2012
DOI: 10.1186/1472-6963-12-142
|View full text |Cite
|
Sign up to set email alerts
|

A reduction in public funding for fertility treatment - an econometric analysis of access to treatment and savings to government

Abstract: BackgroundAlmost all assisted reproductive technology (ART) and intrauterine insemination (IUI) treatments performed in Australia are subsidized through the Australian Government’s universal insurance scheme, Medicare. In 2010 restrictions on the amount Medicare paid in benefits for these treatments were introduced, increasing patient out-of-pocket payments for fresh and frozen embryo ART cycles and IUI. The aim of this study was to evaluate the impact of the policy on access to treatment, savings in Medicare … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
30
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 43 publications
(31 citation statements)
references
References 16 publications
0
30
0
1
Order By: Relevance
“…Almost all ART treatment is eligible for partial re‐imbursement by Medicare, without limitations on the number of cycles or the woman's age. The cost of fresh stimulated ART cycles is estimated to be about $10 000, of which $6000–7000 is reimbursed by Medicare 18 . Several studies have found that the out‐of‐pocket cost of ART treatment for patients influences the number of embryos transferred: higher out‐of‐pockets costs encourage multiple embryo transfers to maximise pregnancy rates with fewer funded cycles 19 , 20 .…”
Section: Discussionmentioning
confidence: 99%
“…Almost all ART treatment is eligible for partial re‐imbursement by Medicare, without limitations on the number of cycles or the woman's age. The cost of fresh stimulated ART cycles is estimated to be about $10 000, of which $6000–7000 is reimbursed by Medicare 18 . Several studies have found that the out‐of‐pocket cost of ART treatment for patients influences the number of embryos transferred: higher out‐of‐pockets costs encourage multiple embryo transfers to maximise pregnancy rates with fewer funded cycles 19 , 20 .…”
Section: Discussionmentioning
confidence: 99%
“…There are large numbers of children without homes, children whose adoption would, in most cases, improve their lives [11]. In addition to being more accessible and affordable than ART, adoption brings with it the social good of giving a child who is without parents a chance to grow up in a loving home and reduces governmental expenditures for that child's support [8].…”
Section: Is Art Legitimately Preferable To Adoption?mentioning
confidence: 99%
“…A number of scholars have also argued that mandating insurance coverage reduces the risks associated with ART and, in the long run, cuts costs that arise from the incentive infertility clinics have to increase the live-birth rate by implanting large numbers of embryos per IVF cycle [8,15,20]. Successful implantation of multiple embryos means the woman requires more monitoring during pregnancy and is more likely to have a preterm delivery, while the infants are at increased risk for complications ranging from cerebral palsy to neurological problems [21].…”
mentioning
confidence: 99%
“…The EMSN benefit was intended to be a patient benefit; it was not intended to be a mechanism for doctors to increase their fees (Australian . Following the introduction of the EMSN, infertility clinics increased fees for a stimulated cycle from $3269 to $4089 per cycle (Metherell, 2005 (Chambers et al, 2012a;Chambers, Van Phong, Zhu, & Illingworth, 2012b;Robotham, 2010). The changes resulted in a significant decline in the number of women having IVF cycles in particular among women 40 years or older (Chambers et al, 2012a).…”
Section: Commodification Of Infertilitymentioning
confidence: 99%
“…Following the introduction of the EMSN, infertility clinics increased fees for a stimulated cycle from $3269 to $4089 per cycle (Metherell, 2005 (Chambers et al, 2012a;Chambers, Van Phong, Zhu, & Illingworth, 2012b;Robotham, 2010). The changes resulted in a significant decline in the number of women having IVF cycles in particular among women 40 years or older (Chambers et al, 2012a). The 21-25% decrease in the number of women of all ages accessing IVF suggests that the additional out-of-pocket expense of approximately $2500 was financially prohibitive for many couples (Chambers, Hoang, & Illingworth, 2013b).…”
Section: Commodification Of Infertilitymentioning
confidence: 99%